Strengths, weaknesses, opportunities and threats of mobile applications in undergraduate nursing: a scoping review protocol - Ana Clara Dantas; Leandro Melo de Carvalho; Bárbara Ebilizarda Coutinho Borges; Cyntia Leenara Bezerra da Silva; Ericles Lopes de Moura; João Pedro Machado de Lima; Allyne Fortes Vitor (PLoS ONE, 2025)
Aim To describe the protocol for a scoping review on the main strengths, weaknesses, opportunities and threats of mobile applications in undergraduate nursing. Background Some studies have shown that mobile applications have been objects of increasing interest in nursing education. Although these technologies offer potential benefits to the educational process, their implementation and use are not always without challenges and implications. In this sense, the SWOT analysis will be used to summarize the strengths, weaknesses, opportunities and threats of those technologies. Design Scoping review protocol, conducted in accordance with JBI guidelines. Method This is a protocol for a scoping review to be carried out following the JBI guidelines, in three phases and in the following data sources: Nursing Database, Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online, Scopus, Web of Science and ScienceDirect, later, Google Scholar and, finally, in the references of the primarily collected studies. The inclusion criteria are studies that addressed the topic of mobile applications in Nursing teaching, available in full, free of charge and without time or language cut-off. The exclusion criteria are studies that did not address the topic, opinion articles, letters to the editor and editorials. The results will be presented through tables and a SWOT chart, with the study variables. Expected Results The results will cover the characterization of the sample studies, followed by a SWOT chart containing the main strengths, weaknesses, opportunities and threats of mobile applications in undergraduate nursing. Conclusion The SWOT analysis will identify strengths and weaknesses, promote self-knowledge and strategies for mobile applications in undergraduate nursing. It can also assist in decision-making, communication with partners and publication, improving scientific research.